Computed tomography colonography: Retrospective comparison of laxative plus barium tagging versus iodinated contrast only for bowel preparation and faecal tagging. Issue 2 (20th February 2019) - Perry, Elisa; Moore, Helen; Reeve, Jane
Abstract: Introduction: There is no consensus as to the most optimal bowel preparation regime for Computed Tomographic Colonography (CTC). Concerns regarding laxative bowel preparation (LBP) include tolerability, adverse effects and complexity of regimen. Two hospitals in Auckland changed CTC bowel preparation from standard LBP to Gastrografin (GG) in 2015. The aim of this study is to retrospectively assess objective and subjective quality measures of these different bowel preparations. Methods: Two study groups were selected retrospectively from patients who underwent CTC at two hospitals in September‐October 2013 (LBP) and September‐ October 2015 (GG). Each study group comprised 60 patients (30 consecutive patients from each hospital). Patients were randomized and anonymized to reduce bias in analysis. Study patients were assessed independently by three experienced Radiologists using a simple grading system derived from the literature. Results: There was significantly less faecal residue ( P  = 0.006) and better faecal tagging ( P  = 0.001) in the right colon in the GG group. There was significantly higher fluid residue in the GG group than the LBP group ( P  = 0.0001), particularly in the right colon, with better fluid tagging in the GG group( P  ≤ 0.0001). Higher Hounsfield Units of residual fluid were observed in the GG group ( P  ≤ 0.0001). There was no statistically significant difference in the subjective quality scores ( P  = 0.219), between the two preparations. Conclusions: This study has demonstrated better faecal cleansing and faecal tagging in the GG group. Higher fluid residue in the GG group was offset by better fluid tagging.